Mosquito-bite infection of humanized mice with chikungunya virus produces systemic disease with long-term effects. - Brianne M Hibl (Public Library of Science (PLoS), 2021)
Chikungunya virus (CHIKV) is an emerging, mosquito-borne alphavirus responsible for acute to chronic arthralgias and neuropathies. Although it originated in central Africa, recent reports of disease have come from many parts of the world, including the Americas. While limiting human CHIKV cases through mosquito control has been used, it has not been entirely successful. There are currently no licensed vaccines or treatments specific for CHIKV disease, thus more work is needed to develop effective countermeasures. Current animal research on CHIKV is often not representative of human disease. Most models use CHIKV needle inoculation via unnatural routes to create immediate viremia and localized clinical signs; these methods neglect the natural route of transmission (the mosquito vector bite) and the associated human immune response. Since mosquito saliva has been shown to have a profound effect on viral pathogenesis, we evaluated a novel model of infection that included the natural vector, Aedes species mosquitoes, transmitting CHIKV to mice containing components of the human immune system. Humanized mice infected by 3-6 mosquito bites showed signs of systemic infection, with demonstrable viremia (by qRT-PCR and immunofluorescent antibody assay), mild to moderate clinical signs (by observation, histology, and immunohistochemistry), and immune responses consistent with human infection (by flow cytometry and IgM ELISA). This model should give a better understanding of human CHIKV disease and allow for more realistic evaluations of mechanisms of pathogenesis, prophylaxis, and treatments.